Analisa Faktor Eksternal Pemanfaatan Internet of Things pada Industri Minyak Kayu Putih - Suyanto Suyanto; Tantri Yanuar Rahmat Syah; Edi Hamdi; Ketut Sunaryanto (Yayasan Literasi Sains Indonesia, 2025)
PT. Fear Densu Farm is a manufacturing company engaged in the eucalyptus oil industry in Indonesia, with a cutting-edge technology-based approach that utilizes the Internet of Things (IoT). This business planning project is designed to create a sustainable, efficient, and innovative eucalyptus oil ecosystem through the integration of digital technology into every aspect of its operations to address the imbalance between demand and supply of eucalyptus oil in Indonesia. This business is rooted in Indonesia's great potential as a producer of essential oils, including eucalyptus oil. With a tropical climate and abundant natural resources, Indonesia has the capacity to become a global leader in this industry. However, various challenges still hinder the progress of this sector, such as low quality raw materials, lack of efficiency in the production process, and dependence on imports to meet domestic needs. This study aims to identify and evaluate external factors that influence the implementation of Internet of Things (IoT) technology in the eucalyptus oil industry, so that it can provide a clear picture of external opportunities and challenges that impact the effectiveness and efficiency of IoT utilization in this